Significant Decrease in Hippocampus and Amygdala Mean Diffusivity in Treatment-Resistant Depression Patients Who Respond to Electroconvulsive Therapy - Yrondi, Antoine; Nemmi, Federico; Billoux, Sophie; Giron, Aurélie; Sporer, Marie; Taib, Simon; Salles, Juliette; Pierre, Damien; Thalamas, Claire; Schmitt, Laurent; Péran, Patrice; Arbus, Christophe (Frontiers in Psychiatry, 2019)
Introduction: The hippocampus plays a key role in depressive disorder and the amygdala is involved in depressive disorder through the key role that it plays in emotional regulation. Electroconvulsive Therapy (ECT) may alter the micro structure of these two regions. Since Mean Diffusivity (MD), is known to be an indirect marker of microstructural integrity (Diffusion Tensor Imaging (DTI) scans), we aim to test the hypothesis that Treatment Resistant Depression (TRD) patients undergoing bilateral ECT exhibit a decrease of MD in their hippocampus and amygdala. Methods: Patients, between 50 and 70 years of age, diagnosed with TRD were recruited from the University Hospital of Toulouse and assessed clinically (Hamilton Depression Rating Scale, HAM-D) and by DTI scans at three time points: baseline; V2 (during treatment); V3 within 1 week of completing ECT. Results: We included 15 patients (all responders). The left and right hippocampi and the left amygdala showed a significant decrease in MD at V3, compared to baseline (respectively: β = -2.78, t = -1.97, p = 0.04; β = -2.56, t = -2, p = 0.04; β = -2.5, t = -2.3, p = 0.04, FDR corrected). MD did not decrease in the right amygdala. Only the left amygdala was significantly associated with a reduction in HAM-D (ρ = 0.55, p = 0.049, FDR corrected). Conclusion: MD is an indirect microstructural integrity marker, which decreases in the hippocampus and the left amygdala, during bilateral ECT. This could be interpreted as a normalisation of microstructural integrity in these structures.